2021
DOI: 10.1101/2021.01.28.428540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of the Long Non-coding RNA OIP5-AS1 Exacerbates Heart Failure in a Sex-Specific Manner

Abstract: BackgroundLong ncRNAs (lncRNAs) are known to influence numerous biological processes including cellular differentiation and tissue development. They are also implicated in the maintenance, health and physiological function of many tissues including the heart. Indeed, manipulating the expression of specific lncRNAs has been shown to improve pathological cardiac phenotypes such as heart failure. One lncRNA studied in various settings is OIP5-AS1 (also known as 1700020I14Rik and Cyrano), however its role in cardi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Future contextual work modulating OIP5‐AS1 in animal models will provide insight into which contexts its dysregulation is a driver of the particular condition, or which are cases of guilt‐by‐association. Intriguingly, studies to date have shown no overt knockout phenotypes in mouse models, 4,132 but instead have revealed elegant roles in specific contexts in the heart and brain, for example, 4,109 suggesting that mechanistic and contextual studies are still needed to fully understand the extent of OIP5‐AS1's functional pleiotropism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future contextual work modulating OIP5‐AS1 in animal models will provide insight into which contexts its dysregulation is a driver of the particular condition, or which are cases of guilt‐by‐association. Intriguingly, studies to date have shown no overt knockout phenotypes in mouse models, 4,132 but instead have revealed elegant roles in specific contexts in the heart and brain, for example, 4,109 suggesting that mechanistic and contextual studies are still needed to fully understand the extent of OIP5‐AS1's functional pleiotropism.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulated by observations of its enrichment in striated muscle and differentiated cardiomyocytes along with reduced expression in the context of heart failure, a recent study examined roles for OIP5‐AS1 using a model of pressure‐overload induced heart failure (Figure 4). 109 CRISPR/Cas9 was used to generate knockout mouse models, which revealed a sex‐specific role for OIP5‐AS1, wherein female mice were more prone to heart failure than male mice 109 . Authors indicated that this sex‐specific difference was tied to changes in cardiomyocyte metabolism in female knockout mice versus scarring and fibrosis, and were also independent of changes in previously identified OIP5‐AS1 modulators such as miR‐7, miR‐29 or HuR 109 .…”
Section: A Single Lncrna: a Myriad Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of well-annotated functional motifs in most LncRNAs renders CRISPR targeting of this class of genes in the mouse challenging, though not insurmountable (Miano et al 2019 ). Indeed, several LncRNAs have been targeted with CRISPR in rodents through large deletions of multiple exons or the entire LncRNA locus (Han et al 2014 ; Zhou et al 2021b ; Zhuang et al 2021 ). The approach of removing such large sequences runs the risk of deleting regulatory elements or small intronic RNAs that may compromise accurate interpretation of phenotypes.…”
Section: Genome Editing Of Lncrnas In Micementioning
confidence: 99%